(untitled) (Fiep Bulletin - online, 2016)
The passes are used in basketball to provide a good condition to pitch and as an instrument of maintaining possession. In this sense, the objective of this study was to observe the relationship between the number of passes made ??and the result of hostile action in male adult basketball. To achieve the goal we adopted a qualitative research, which was formed from a sample of six videos of male basketball games held during the London Olympics 2012, belonging to the quarter-finals, semifinals and final. The means of the distributions of passes per game and the hit percentage of pitches in relation to the number of passes were calculated. Furthermore, we verified the existence of differences in the number of passes by Armed Attack (AA) between periods of play. Results show that 73% of the attacks were completed after one, two or three passes, the average being equal to 2.69 passes by AA. The highest percentage of pitch were achieved after changing three- and four passes, respectively, 50.7% and 50.0%. Differences in the distribution of the number of passes by AA among the four periods of play were found. Therefore, the study concludes that a relatively small amount of passes by AA appears to be linked to the characteristics of the players of this technical level and the use of certain collective tactics.